Parental Blessing and Family Conflict: A Case Study of Silariang in Gowa Regency - Fadilah, Nurul; Nurdin, Muh. Nur Hidayat; Zainuddin, Kurniati (Jurnal Psikologi Terapan, 2023)
This study aims to explore the differences in the decision-making process between male and female respondents in dealing with the silariang incident, as well as to analyze the factors influencing their decisions. In this research, two respondents, namely respondent HT (male) and respondent DK (female), were the main focus to understand the differences in thinking styles and decision-making processes. The research method employed was a qualitative approach with descriptive analysis, including in-depth interviews to explore the respondents' decision-making process. The results show that respondent HT adopts a perfect rational thinking model, making decisions quickly and logically, while respondent DK is more emotional, takes more time, and makes impulsive decisions. Despite these differences, both respondents ultimately made the same decision, which was to give their blessing to their child who was involved in silariang. This decision was considered the best option, taking into account the child's happiness and maintaining family harmony. This study also highlights the importance of self-reflection in parental decision-making and the impact of thinking styles and gender on the decision-making process. The implications of this research suggest that, in emotionally charged situations, a more rational and critical decision-making approach can help parents face challenges more thoughtfully.